Harmonic Analysis of Multipath Index Time Series in GPS Stations - Souza, Eniuce Menezes de; Alves, Daniele Barroca Marra; Schumacher, Fernanda Lang (Trends in Computational and Applied Mathematics, 2015)
The identification of the cyclical and seasonal variations can be veryimportant in time series. In this paper, the aim is to identify the presence ofcyclical or seasonal variations in the indices of the multipath effect on continuousGPS (Global Positioning System) stations. Due to the model used to obtain theseindices, there should not have cyclical variations in these series, at least due to themultipath effect. In order to identify the presence of cyclical variations in theseseries, correlograms and Fourier periodograms were analyzed. The Fisher test forseasonality was applied to confirm the presence of statistical significant seasonality.In addition, harmonic models were adjusted to check in which months of the yearthe cyclical effects are occurring in the multipath indices. The possible causes ofthese effects are pointed out, which will direct the upcoming investigations, as wellas the analysis and correlations of other series. The importance of this analysisis mainly due to the fact that errors in the collected signals of these stations willdirectly influence the accuracy of the results of the whole community that directlyor indirectly uses GPS data.